Pharmaceutical anti-counterfeiting : combating the real danger from fake drugs - Davison, Mark, 1968 March 1- (Hoboken, N.J. : John Wiley & Sons, 2011)
This book overviews and integrates the business and technical issues that pharmaceutical companies need to know in order to combat the major global problem of counterfeit medicines. In addition to discussion of the problems, the author Davison addresses analytical techniques scientists use to detect counterfeits and presents some possible solutions to the threat of counterfeit medical products. Coverage moves from basic overview of the problem, costs / risks to consumers (toxic products, mistrust of drug companies) and business (revenue loss, public trust), government oversight and regulation, authentication strategies (packaging, analytical techniques), product tracking and supply chain, and case studies from around the globe.
Frontmatter -- General Themes. Introduction -- Origins and Context of Counterfeiting in Healthcare -- A Snapshot of the Problem -- Risks and Costs of Counterfeit Pharmaceuticals -- Anti-Counterfeiting Definitions -- Protecting and Educating Consumers -- Business Risks and Strategy -- Government Issues -- Intellectual Property and Anti-Counterfeiting -- Traceability or Authentication? -- Authentication. What is Authentication? -- Authentication of the Person -- Authentication of Bulk Products -- On-Dose and In-Dose Authentication -- Analytical Detection of Counterfeit Dosage Forms -- The Role of Packaging -- Printing Technologies -- Security Labels -- Holograms and DOVIDs -- Specialty Inks -- Covert Taggants and Forensic Markers -- General Conclusions on Printed Packaging and Security Labels -- Security of Primary Packaging -- Security of Secondary Packaging -- Analytical Methods for Packaging -- Security of Other Packaging Types -- Bulk Packaging and Transport Security -- Product Tracking. Rationale for Pharmaceutical Tracking -- Tracking Technologies -- Data Format, Generation, and Storage -- Management of Packaging Hierarchy -- Geographical Perspectives -- Product Tracking in Other Industries -- Supply Chain Security Processes -- Implementing Anti-Counterfeiting Initiatives-Practical Issues -- Conclusions and the Future. Where do we go from here? -- New Models, New Approaches -- Selected Examples from around the World -- Further Resources. A Patient's Guide to Avoiding Counterfeit Drugs -- Notes and References -- Glossary -- Further Resources. Information Sources -- Drug Regulators.
Includes bibliographical references and index.
Print version record.
Keywords: Product counterfeiting; Drug adulteration; Drug Contamination; Consumer Product Safety; Fraud -- prevention & control; Pharmaceutical Preparations -- standards; Drug adulteration; Product counterfeiting; MEDICAL -- Drug Guides; MEDICAL -- Nursing -- Pharmacology; MEDICAL -- Pharmacology; MEDICAL -- Pharmacy; Drug adulteration; Product counterfeiting; Electronic books